ANALISIS PENGARUH MARKETING MIX TERHADAP PENGAMBILAN KEPUTUSAN NASABAH MENABUNG PADA BANK JATENG CABANG UNGARAN - Dyah Ayu Annurfa; Aris Sunindyo (KEUNIS, 2020)
This research is aimed to analyze and identify the signification influence of product ,price, promotion and place to the saving deccison at Bank Jateng Cabang Ungaran and partially. Data were collected through questionnaires to 100 respondents who are customers of saving at Bank Jateng Cabang Ungaran. Which is obtained by using purposive sampling technique. The calssical assumption of normality test,multicoloniarity, heteroscedasticity test and multiople linier analysis test and coefficient of determination. The hypothesis proved using the t and F test. The results of this study indicate that the product, price, promotion, placesimultaneously have significanctly influence against the customer’s decision to save. Partially there are one significant variabels that influence the customer decision saving of promotion. For product, price, place variables not significant on the customer’s decision to save at Bank Jateng Cabang Ungaran